INCIDENCE AND PREVALENCE OF VARIOUS PSYCHIATRIC DISORDERS IN PSYCHIATRIC DEPARTMENT OF TEACHING BASED HOSPITAL ONGOLE: A PROSPECTIVE OBSERVATIONAL STUDY - T. Josna, T. Josna; N. Rajesh, N. Rajesh; K. Naga Sindhura, K. Naga Sindhura; K. Hema Ravali, K. Hema Ravali; N. Uma Jyothi, N. Uma Jyothi; G, Venkata Nagaraju (International Journal of Indigenous Herbs and Drugs, 2020)
Background: Psychiatric disorders are known to vary across time within the same population and also vary across populations. Most of the community-based Indian epidemiological studies are on point prevalence. The adult epidemiological finding that mental disorders have early ages of onset has created interest in the minds of psychiatrists. Children and adolescents are at high risk of developing mental disorders. Aim & objective: we are aimed at to conduct of this study was to know the overall incidence and prevalence rate of various Psychiatric disorders in the Psychiatric department of teaching based hospitals and the objective of the study is to find out the incidence and prevalence of the predominant psychiatric disorder. To find the role of key factors like age, Education, Gender, environmental analysis, Marital status, and sleep pattern on the mental health status of Patients. Material & Methods: This study was conducted on 500 patients, both male and female were included in the study. ICD- 10 and DSM IV criteria tools were used. Statistical Analysis was done using appropriate tests like the “t” test and Chi-Square test. Results: A total of 500 Patients we are included in our study, males are 293(59%) and Females are 207 (41%). Depression shows the highest incidence of 7.0%. Schizophrenia shows the highest prevalence (17.6%) Chi-Square analysis indicated no significant difference in prevalence between the number of males and females. There were no significant differences among the prevalence rates among the participants who belonged to middle-class urban and rural areas. Conclusion: Psychology is the science of behavior and mind, it intends to surmise clinical individuals and groups via placing general principles and researching specific cases. As a responsible clinical pharmacist, we have played a major role in the effective counseling of patients by using counseling aids. In this research, have a leading prevalence plus incidence of psychiatric disorders are detected.